Resveratrol in the Treatment of Gynecological Cancer: Mechanisms and Therapeutic Potential - Mozafaryan, Mohammad Javad; Rezaei, Pouria; Masoudpoor, Fardin; Bahri, Amirmohammad; Samini, Mohammad; Farkhondeh, Tahereh; Pourhanifeh, Mohammad Hossein; Samarghandian, Saeed (Current Medicinal Chemistry, 2025)
Gynecological cancers, encompassing endometrial, ovarian, and cervical cancer, pose significant challenges in clinical practice, often marked by high mortality rates and treatment resistance. Despite advances in standard therapies, including chemoradiation and surgery, tumor recurrence and metastasis remain formidable obstacles. In this context, there is a pressing need to explore novel therapeutic strategies that offer improved efficacy and reduced side effects. Herbal medicine, particularly compounds like resveratrol, has garnered attention for its diverse biological properties, including anticancer effects. Resveratrol, a multipotential nutraceutical, holds promise in gynecological cancer therapy through its modulation of key cellular and molecular processes. This review aims to provide an overview of the current status, challenges, and opportunities in utilizing resveratrol for gynecological cancer treatment. We discuss its role in miRNA regulation, clinical trial findings, and the development of effective formulations. By elucidating the underlying mechanisms of resveratrol's anticancer effects and exploring innovative delivery systems, we aim to shed light on the potential avenues for optimizing its therapeutic benefits in gynecological cancers.
Keywords: endometrial cancer